Modeling of Electric Disturbance Signals Using Damped Sinusoids via Atomic Decompositions and Its Applications. (5th March 2007) - Lovisolo Lovisolo, Lisandro Lisandro; Tcheou Tcheou, Michel P. Michel P.; da Silva da Silva, Eduardo A. B. Eduardo A. B.; Rodrigues Rodrigues, Marco A. M. Marco A. M.; Diniz Diniz, Paulo S. R. Paulo S. R.
Abstract : The number of waveforms monitored in power systems is increasing rapidly. This creates a demand for computational tools that aid in the analysis of the phenomena and also that allow efficient transmission and storage of the information acquired. In this context, signal processing techniques play a fundamental role. This work is a tutorial reviewing the principles and applications of atomic signal modeling of electric disturbance signals. The disturbance signal is modeled using a linear combination of damped sinusoidal components which are closely related to the phenomena typically observed in power systems. The signal model obtained is then employed for disturbance signal denoising, filtering of "DC components, " and compression.